Rasm Mushaf Usmany Dan Rahasianya (Sebuah kajian tentang bukti. baru kemu'jizatan AI-Qur'an) - Aziz, Abdul (ULUL ALBAB Jurnal Studi Islam, 2003)
Syalabi wrote, in his book that Abu Bakar has collected Al-Qur'an comprising seven readings which are allowed to be read. He did not specify on one certain reading. A lot of his friends also had their own mushaf. The differences, then, caused the different reading among Iraq and Syam society. This dispute made Khudzaifah bin al-Yaman was angry. He informed it to Usman bin Affan r.a. and finally Usman united the people in one letter or one reading and Rasm.